Detection of earnings manipulation in S-share firms listed on the Singapore stock exchange - Chen, Edison Haoyang (2011)
This paper examines the nature of China firms listed on the Singapore Stock Exchange. The main aim is to determine whether high probability of earnings manipulation is a common phenomenon amongst S-share firms. We also examine the reliability of various predictors such as Healy’s [1999] earnings manipulation incentives, to predict the probability of S-shares firms manipulating earnings. The motivations for researching into these topics were to pioneer research in an area that is lacking, and to provide deeper insights to the various stakeholders of S-share firm. Firm-level data was analyzed to build Beneish [1997]’s M-Score Model, and a T-test was used afterwards to determine whether S-share firms exhibit high probability of earnings manipulation. Linear regression was subsequently used in determining the effect of predictors on probability of earnings manipulation by the S-share firms. A total of 102 S-share firms with four year of complete data were analyzed using the calculated M-Score values from 2007 to 2009 as shown in Appendix 1.The results suggest that the phenomenon of high earnings manipulation probability is systematic across S-share firms. The findings suggest that investors to be cautious about pricing S-share firms without taking into account the systematic risk of earnings manipulation. Also, an interesting observation shows significantly higher M-Score for the S-share firms during the recession year of 2008. Furthermore, the firm’s listing age can be used to predict the likelihood of earnings manipulation in S-share firms; shorter listing age is found to have a higher M-Score.